1999
DOI: 10.1161/01.atv.19.8.1872
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Inhibition by Interleukin-6 of the Class A Macrophage Scavenger Receptor in Macrophages Derived From Human Peripheral Monocytes and the THP-1 Monocytic Cell Line

Abstract: Abstract-Expression of the class A macrophage scavenger receptor (MSR) contributes to the uptake of modified low density lipoproteins (LDL) by macrophages and transformation of these cells into lipid-laden foam cells, which characterize atherosclerosis. Many environmental factors, in particular, proinflammatory cytokines and growth factors, can exert regulatory effects on MSR expression, whereas intracellular accumulation of cholesterol itself does not influence MSR levels to any considerable extent. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
(45 reference statements)
1
24
0
2
Order By: Relevance
“…IL-6 and IL-10 have also been previously shown to inhibit macrophage foam cell formation (27,28,30,31). IL-6 reduces AcLDL uptake by inhibiting SR gene expression (27), whereas IL-10 decreases foam cell formation by various mechanisms (28,30,31), some of which remain controversial (31). Our results demonstrate a clear cut mechanism by which IL-33 inhibits macrophage foam cell formation.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…IL-6 and IL-10 have also been previously shown to inhibit macrophage foam cell formation (27,28,30,31). IL-6 reduces AcLDL uptake by inhibiting SR gene expression (27), whereas IL-10 decreases foam cell formation by various mechanisms (28,30,31), some of which remain controversial (31). Our results demonstrate a clear cut mechanism by which IL-33 inhibits macrophage foam cell formation.…”
Section: Discussionsupporting
confidence: 58%
“…IL-33 decreases both AcLDL/OxLDL uptake and intracellular total and esterifed cholesterol levels but enhances cholesterol efflux through regulation of key genes involved in modified LDL uptake, cholesterol efflux/transport, and the storage of cholesteryl esters and triglycerides. IL-6 and IL-10 have also been previously shown to inhibit macrophage foam cell formation (27,28,30,31). IL-6 reduces AcLDL uptake by inhibiting SR gene expression (27), whereas IL-10 decreases foam cell formation by various mechanisms (28,30,31), some of which remain controversial (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study and other reports have demonstrated that a significantly elevated transforming growth factor ␤1 level in prostate cancer cells is associated with tumor progression and metastasis (41)(42)(43). Interleukin 6 has also been reported recently to be capable of inhibiting SR-A expression in THP-1 cells at both mRNA and protein levels (44). Interestingly, there is accumulating evidence that interleukin 6 expression in cancer cells is progressively increased with increasing malignant potential and positively associated with metastasis (45,46).…”
Section: Discussionmentioning
confidence: 75%
“…Several cytokines were previously shown to modulate the formation of foamy macrophages generated in the presence of aggregated, acetylated or oxidized LDL. IFN-␥ , IL-1 ␤ , and TNF-␣ promote macrophage foam cell formation (25)(26)(27)(28), while IL-6, TGF-␤ 1, and IL-33 (29)(30)(31) have been described as anti-foam cell cytokines in humans and IL-10 facilitates both cholesterol uptake and effl ux in macrophages ( 32 ). Only IL-1 ␤ expression was weakly affected by IL-17A treatment, suggesting a role for this models.…”
Section: Discussionmentioning
confidence: 97%